2022
DOI: 10.1111/liv.15152
|View full text |Cite
|
Sign up to set email alerts
|

Preneoplastic lesions in the liver: Molecular insights and relevance for clinical practice

Abstract: Hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA) are the most frequent primary liver cancers, accounting for approximately 80% and 15%, respectively. HCC carcinogenesis occurs mostly in cirrhosis and is a complex multi-step process, from precancerous lesions (low-grade and high-grade dysplastic nodules) to progressed HCC.During the different stages of liver carcinogenesis, there is an accumulation of pathological, genetic and epigenetic changes leading to initiation, malignant transformation and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 143 publications
(363 reference statements)
0
22
0
Order By: Relevance
“…First, in the context of the above considerations, the absence of malignancy could not be ascertained in such cases, so they could be used for neither the calculation of sensitivity (which required cancer-diagnosed subjects) nor the calculation of specificity (which required subjects without a diagnosis or a suspicion of cancer). Second, it has been established in human oncology that patients with a history of benign masses have an elevated relative risk of malignancy in multiple organs, such as breast [ 97 , 98 ], uterus [ 99 ], colon [ 100 ], and liver [ 101 , 102 ]. For perspective, two recent large clinical validation studies for MCED tests intended for use in humans also excluded potentially confounding cases (such as those with high-grade dysplasia or with suspected but unconfirmed cancer status at the time of blood collection) from their analysis, and neither study provided an analysis of subjects with benign tumors [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, in the context of the above considerations, the absence of malignancy could not be ascertained in such cases, so they could be used for neither the calculation of sensitivity (which required cancer-diagnosed subjects) nor the calculation of specificity (which required subjects without a diagnosis or a suspicion of cancer). Second, it has been established in human oncology that patients with a history of benign masses have an elevated relative risk of malignancy in multiple organs, such as breast [ 97 , 98 ], uterus [ 99 ], colon [ 100 ], and liver [ 101 , 102 ]. For perspective, two recent large clinical validation studies for MCED tests intended for use in humans also excluded potentially confounding cases (such as those with high-grade dysplasia or with suspected but unconfirmed cancer status at the time of blood collection) from their analysis, and neither study provided an analysis of subjects with benign tumors [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The malignant development of HCC is a complicated biological process, including hyperproliferation of tumor cells in situ, remodeling and degradation of the extracellular matrix, stromal and vascular invasion, resistance to anoikis and distant metastasis [30,31] . Identifying novel and effective biomarkers will improve current therapeutic strategies for HCC and prolong the survival of patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low prevalence of these mutations in DN suggests that they play a more critical role in tumor progression in cirrhosis than in the onset of carcinogenesis [ 28 , 29 ]. Chromosomal alterations, such as copy number variants, have been described in precancerous lesions, mainly including increases or deletions of chromosome 8 arms (8p or 8q) and increases in 1q [ 30 ]. An analysis of the prevalence of SCNAs at the arm level showed that 1q+ and 8q+ were common in HCC, uncommon in DN, and least common in cirrhosis [ 31 , 32 ].…”
Section: Molecular and Genetic Mechanism Of Hepatocarcinogenesismentioning
confidence: 99%